Pewne Rozwiązania dla Kołowych Płyt Trójwarstwowych Obciążonych Osiowo-Symetrycznie - J. Gołaś (Engineering Transactions, 1971)
Solutions are given in this paper for three-layer circular plates freely supported on the whole circumference, subjected to the action of an axially-symmetrical load. A loading by condensed force and continuous load over the entire region of the plate is considered. It is assumed that the plate is symmetrical with respect to its central plane, that the external layers of the plate satisfy all the assumptions of the theory of shields and thin isotropic plates, and that the central layer is incompressible and exhibits only rigidity to deformations of shape in the direction normal to the surface on the central plate.